The Students’ Difficulties in Writing Verbal and Nominal Sentence at the Second Semester of STKIP Insan Madani Airmolek - Puspa Gundary; Gusparia; Neni Triana; Robi Wismanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Writing in English can make students very enthusiastic about learning because writing requires a lot of things so that writing can be accepted academically. Not all students can write correctly. So, this is the author's motivation to find out the ability and the factors that influence of student difficulty in writing verbal and nominal sentence. The subjects of this research were 24 students. The method used in this research is descriptive research with qualitative and quantitative analysis techniques. The score of the quiz result were categorized fair good. Afterwards, the internal factors shown that the students were bad mood to learn English, not ready to learn English, they claimed English language is bored and they felt sleepy while learned English. Finally, the external factors shown that they didn’t like make a group discussion because couldn’t be focus on materials, the teacher not explained well and they confused the methods used